Improving Mathematics Learning Results on Multiplication Material Using the Teams Game Tournament Learning Method in Class IV Madrasah Ibtidaiyah - Elly Fatmawati; Mehdi Izadi (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: The purpose of this research is to improve learning outcomes and meet the target of achieving the minimum completeness criteria for mathematics regarding multiplication calculation operations using the teams game tournament learning method in class IV Madrasah Ibtidaiyah Kawengen, East Ungaran sub-district, Semarang Regency. Methodology: This research is Classroom Action Research with planning, action, observation and reflection steps carried out in three cycles. The research was carried out in class IV at Madrasah Ibtidaiyah Kawengen with a total of 19 students. Main Findings: Based on the results of research conducted at Madrasah Ibtidaiyah Kawengen, East Ungaran District, Semarang Regency, it can be concluded that the teams game tournament learning method can improve learning outcomes and can meet the target of achieving the minimum completeness criteria for mathematics multiplication calculation operations in class IV students. This is evidenced by an increase in the completeness of mathematics learning outcomes in each cycle and the achievement of a percentage of mathematics learning outcomes that classically exceeds the minimum completeness criteria achievement limit. Novelty/Originality of this study: The novelty of this research is the application of the Teams Game Tournament learning method to improve mathematics learning outcomes in multiplication material.